2002
DOI: 10.1002/rra.693
|View full text |Cite
|
Sign up to set email alerts
|

Controls on the size and occurrence of pools in coarse‐grained forest rivers

Abstract: Controls on pool formation are examined in gravel-and cobble-bed rivers in forest mountain drainage basins of northern California, southern Oregon, and southeastern Alaska. We demonstrate that the majority of pools at our study sites are formed by flow obstructions and that pool geometry and frequency largely depend on obstruction characteristics (size, type, and frequency). However, the effectiveness of obstructions to induce scour also depends on channel characteristics, such as channel gradient, width:depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
192
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(197 citation statements)
references
References 86 publications
4
192
0
1
Order By: Relevance
“…The shape and orientation of constrictions also influences pool characteristics. Buffington et al (2002) found that the largest, best developed pools were created by vertical versus horizontal constrictions. Lisle (1986) found that deflection angle of the flow at an obstruction influenced pool development.…”
Section: The Influence Of Channel Constrictions On Pool-riffle Characmentioning
confidence: 98%
See 3 more Smart Citations
“…The shape and orientation of constrictions also influences pool characteristics. Buffington et al (2002) found that the largest, best developed pools were created by vertical versus horizontal constrictions. Lisle (1986) found that deflection angle of the flow at an obstruction influenced pool development.…”
Section: The Influence Of Channel Constrictions On Pool-riffle Characmentioning
confidence: 98%
“…Channel obstructions generate flow convergence and subsequent forced pools (Lisle, 1986;Montgomery et al, 1995;Thompson et al, 1999;Buffington et al, 2002;MacWilliams et al, 2006). In channels with forced pools, over 80% of pools are associated with structural controls and large obstructions that include boulders, bedrock outcrops and large woody debris (Dolan et al, 1978;Lisle, 1986;Montgomery et al, 1995;Thompson, 2001).…”
Section: Formation Of Forced Pools and Rifflesmentioning
confidence: 99%
See 2 more Smart Citations
“…These impoundments typically fill with sediment to form steps and force nominally bedrock channels to be alluvial (Montgomery et al, 1996(Montgomery et al, , 2003bMassong and Montgomery, 2000; figure 2). Wood thus affects amounts and patterns of sediment storage in drainage networks (Swanson and Lienkaemper, 1978;Marston, 1982;Nakamura and Swanson, 1993;Lancaster et al, 2001;May and Gresswell, 2003) and also affects smaller features such as the locations and morphologies of pools (Buffington et al, 2002). Montgomery et al (2003a) surmised that the relative immobility of large wood, its impounding of sediment, and the concomitant shielding of the underlying bedrock decrease the effective bedrock erodibility and, hence, steepen the longitudinal channel profile.…”
Section: Introductionmentioning
confidence: 99%